Interchangeable Concept of Cognitive Styles and Learning Styles: a Conceptual Analysis - Zainudin Abu Bakar; Rafaquat Ali (Intelektual Pustaka Media Utama, 2018)
Inquiries into the nature and effects of cognitive and learning style constructs are mounting daily, regardless of criticism and confusion about the boundaries, natures and to some extent overlapping issues of these two constructs. These issues raise several questions about the credibility of these two constructs with regard to further research, application and development. Therefore, there is a need to crystallize their natures to pave the way for further research and for a better understanding of individual’s learning. The current scientific review strengthens the concept of these two constructs as separate and independent, each contributing in its own way to different fields of human learning. Both constructs have different histories and schools of thought directed toward different ends. The relationship of these constructs undeniably establishes their usefulness and value as research subjects. However, specific concerns is required in defining cognitive and learning styles which may hinder the credibility and usefulness of further research, including valid and reliable measurements, cohesive theory, application oriented studies, use of multiple methods in research, and the origin and development of these constructs. This article explores the discourse in these fields and highlights potential issues with the constructs to assist researchers in constructing a more comprehensive understanding of the research framework.